EXPERIMENT ON EFFECTS OF LOE-PROTEIN DIET SUPPLEMENTED WITH α-KETOACIDS ON HYPERTROPHY OF DIABETIC GLOMERULUS AND ITS RELATIONSHIP WITH THE LEVEL OF CYCLIN KINASE INHIBITOR P27 - Yi Zhou; Weijie Yuan; Ting Dong; Ling Wang (The Korean Society of Nephrology, 2012)
Low-protein diet supplemented with α-keto acids was reported to have renoprotective roles in diabetic nephropathy via inhibiting glomerular hypertrophy, however, the mechanism has not yet been fully clarified. the cyclin kinase inhibitor p27 play an important role in hypertrophy of diabetic glomerulus, The objective of the present study was to investigate the relationship between the cyclin kinase inhibitor p27 and the effect of low-protein diet supplemented with α-keto acids on hypertrophy of diabetic glomerulus in rats. STZ-induced diabetic rats were given low-protein diet(5□ protein in fodder, LPD group)or low-protein diet supplemented with α-keto acids(5□ protein in fodder including 1□ protein supplied by α-keto acids, LPD+α-KA group)or normal-protein diet(10□protein in fodder, NPD group)for 8 weeks□The p27 protein of glomerular lysate was detected with Western Blot. The extracellular matrix (ECM)protein(type IV collagen and fibronectin) of glomerular lysate and 24 h urine albumin were examined with ELISA□ Image analysis system was used to detect the diameter of each glomerulus. Glomerular p27 protein increased in diabetic rats no matter what kinds of diet were given, meanwhile,the 24h urine albumin, glomerular ECM,glomerular diameter elevated as well as the ratio of kidney weight over body weight in diabetic rats□Both low-protein diet and low-protein diet supplemented with α-keto acids could attenuate changes occurred in diabetic rats with normal-protein diet□Glomerular p27 level(8.6±2.3 vs 11.1±3.6,P〈0.01),24 h urine albumin(13.21±2.49)μg□24 h vs (18.13±3.23)μg□24 h,P〈0.01,glomerular diameter(652±73)μm2 vs (721±75)μm2,P〈0.05,and the ratio of kidney weight over body weight(11.02±1.72 vs 12.03±1.85,P〈0.05)were lower in LPD+α-KA group than LPD group. Solely glomerular p27 level was linearly related with the ratio of kidney weight over body weight in diabetic rats□The blood glucose and serum albumin remained constant in diabetic rats no matter what kinds of diet were given. In conclusion, Low-protein diet supplemented with α-keto acids can further inhibit glomerular hypertrophy,and may protect diabetic glomerulus through decrease of glomerular p27 level.